Two-part cyanoacrylate / free radical curing adhesive system.

The two-part cyanoacrylate/free radical curable adhesive system, featuring a core-shell impact modifier and a gradient polymer layer, addresses the challenge of improving impact strength and durability while maintaining fast fixation and wide substrate compatibility, achieving superior performance under extreme conditions.

JP7671283B2Active Publication Date: 2025-05-01HENKEL KGAA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022520190
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-10-01
Publication Date
2025-05-01
Estimated Expiration
2040-10-01

AI Technical Summary

Technical Problem

Existing cyanoacrylate and free radical curable adhesive systems face challenges in achieving improved impact strength, especially under extreme conditions such as high temperature and high relative humidity, while maintaining fast fixation time and wide substrate compatibility.

Method used

A two-part cyanoacrylate/free radical curable adhesive system is developed, comprising Part 1 with cyanoacrylate components and a peroxide catalyst, and Part 2 with a free radical curable component and a transition metal. The system includes a core-shell impact modifier with a polymer core and multiple polymer layers, each with a different composition, and at least one gradient polymer layer.

Benefits of technology

The system exhibits enhanced impact toughness, improved fixation time, and better durability performance compared to traditional two-part adhesive systems, while maintaining strong adhesion across a wide range of substrates and resisting extreme environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671283000017
    Figure 0007671283000017
  • Figure 0007671283000001
    Figure 0007671283000001
  • Figure 0007671283000002
    Figure 0007671283000002
Patent Text Reader

Abstract

A two-part cyanoacrylate / free radical curable adhesive system is provided that exhibits improved impact strength performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] A two-part cyanoacrylate / free radical curable adhesive system is provided that exhibits improved impact strength performance. [Background technology]

[0002] (Brief Description of Related Art) Curable compositions such as cyanoacrylate adhesives are well recognized for their excellent ability to rapidly bond a wide range of substrates, generally within minutes, and often within seconds, depending on the particular substrate.

[0003] The polymerization of cyanoacrylates is initiated by nucleophiles found under normal atmospheric conditions on most surfaces. Initiation by surface chemistry means that sufficient initiating species are available when two surfaces are in intimate contact with a small layer of cyanoacrylate between the two surfaces. Under these conditions, a strong bond can be obtained in a short time. Thus, in essence, cyanoacrylates often function as instant adhesives.

[0004] The performance, especially durability, of cyanoacrylate adhesives is often questionable when exposed to high temperature and / or high relative humidity conditions. To combat these application-dependent shortcomings, many additives have been identified for inclusion in cyanoacrylate adhesive formulations. Improvements are still considered beneficial.

[0005] A variety of additives and fillers have been added to cyanoacrylate compositions to modify their physical properties.

[0006] For example, Serniuk et al., US Pat. No. 3,183,217, discloses the free radical polymerization of methacrylic acid or methyl methacrylate monomers with non-polar or low polarity olefins, the monomers being complexed with Friedel-Crafts halides.

[0007] Takeshita, U.S. Patent No. 3,963,772, discloses liquid telomers of alkylene and acrylic monomers which result in short chain alternating copolymers substantially terminated at one end of the polymer chain with the more reactive alkylene unit. The liquid telomers are useful for producing elastomeric polymers for high molecular weight rubbers which, due to their liquid phase, allow for the easy incorporation of fillers, additives, etc.

[0008] O'Connor, U.S. Patent No. 4,440,910, is directed to cyanoacrylate compositions having improved toughness achieved by the addition of an elastomer, i.e., an acrylic rubber. These rubbers are either (i) homopolymers of alkyl esters of acrylic acid, (ii) copolymers of alkyl or alkoxy esters of acrylic acid with another polymerizable monomer such as a lower alkene, (iii) copolymers of alkyl esters of acrylic acid, (iv) copolymers of alkoxy esters of acrylic acid, and (v) mixtures thereof.

[0009] No. 4,560,723 to Millet et al. discloses a cyanoacrylate adhesive composition that includes a toughening agent that includes a core-shell polymer and a sustainer that includes an organic compound that includes one or more unsubstituted or substituted aryl groups. The sustainer is reported to improve toughness retention after heat aging of the cured bond of the adhesive. The core-shell polymer is treated with an acid wash to remove any impurities that may cause polymerization, such as salts, soaps, or other nucleophilic species remaining from the manufacturing process of the core-shell polymer.

[0010] Mitry, U.S. Pat. No. 5,340,873, discloses cyanoacrylate adhesive compositions having improved toughness by including an effective reinforcing amount of a polyester polymer derived from a dibasic aliphatic or aromatic carboxylic acid and a glycol.

[0011] Ohsawa et al., U.S. Pat. No. 5,994,464, discloses a cyanoacrylate adhesive composition comprising a cyanoacrylate monomer, an elastomer that is miscible or compatible with the cyanoacrylate monomer, and a core-shell polymer that is compatible, but not miscible, with the cyanoacrylate monomer.

[0012] Wojciak, U.S. Patent No. 6,833,196, discloses a method for enhancing the toughness of a cyanoacrylate composition between steel and an EPDM rubber substrate. The disclosed method is defined by the following steps: providing a toughening agent comprising a methyl methacrylic monomer and at least one of a butyl acrylic monomer and an isobornyl acrylic monomer providing a cyanoacrylate component, whereby the acrylic monomer toughening agent enhances the toughness of the cyanoacrylate composition, and upon curing, the cyanoacrylate composition has an average tensile shear strength of about 4400 psi or greater after 72 hours at room temperature cure and 2 hours post cure at 121°C.

[0013] Reactive acrylic adhesives, which cure by free radical polymerization of (meth)acrylic acid esters (i.e., acrylates), are known but suffer from certain drawbacks. Commercially important acrylic adhesives, especially those made from methyl methacrylate, tend to have an unpleasant odor. Methyl methacrylate-based acrylic adhesives also have low flash points (approximately 59°F). The low flash point is a particular problem during storage and transportation of the adhesive. If the flash point is below 141°F, the U.S. Department of Transportation classifies the product as "flammable," requiring marking and special storage and transportation conditions.

[0014] Righettini's U.S. Pat. No. 6,562,181 aimed to provide a solution to the problem addressed in the previous paragraph by describing an adhesive composition comprising (a) a trifunctional olefinic first monomer comprising an olefinic group having at least three functional groups attached directly to an unsaturated carbon atom of the olefinic group, (b) an olefinic second monomer copolymerizable with the first monomer, (c) a redox initiator system, and (d) a reactive diluent, wherein the composition is liquid at room temperature, 100% reactive, substantially free of volatile organic solvents, and curable at room temperature.

[0015] More recently, U.S. Patent No. 9,371,470 to Burns describes and claims a two-part curable composition including (a) a first part including a cyanoacrylate component and a peroxide catalyst, and (b) a second part including a free radically curable component and a transition metal. When mixed together, the peroxide catalyst initiates cure of the free radically curable component, and the transition metal initiates cure of the cyanoacrylate component. In particular, in one embodiment, the peroxide catalyst is t-butyl perbenzoate.

[0016] In an unrelated art, U.S. Patent No. 9,068,036 (Navarro) is directed to and claims a thermoplastic polymer composition comprising a) one thermoplastic polymer, and b) a core-shell impact modifier obtained by a process including the following steps: i) synthesizing a core-shell copolymer latex by emulsion polymerization, ii) controlling and adjusting the pH value of the core-shell polymer particles after the synthesis step, iii) coagulating the core-shell polymer at a pH of 4 to 8 by addition of an aqueous electrolyte solution, the resulting core-shell impact modifier comprising a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer comprising a polymer that is a gradient polymer, the gradient polymer being a copolymer consisting of at least two different monomers (A) and (B) and having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer.

[0017] U.S. Patent No. 9,714,314 (Navarro) is directed to and claims core-shell copolymer impact modifier particles having a particle size of 170-350 nm and a pH of 6-7.5, comprising one polymer rubber core comprising at least partially crosslinked isoprene or butadiene and optionally styrene, and at least two polymer layers, at least one of which is an outermost thermoplastic shell layer having a Tg greater than 25°C, each layer having a different polymer composition, at least one of which is a gradient zone produced in a polymerization stage reaction in which mostly styrene first monomer is incorporated during the early stages of polymerization while increasing amounts of methyl methacrylate second monomer are added until mostly or completely methyl methacrylate is incorporated during the final stage polymerization, forming a gradient zone, and wherein the glass transition temperature of the polymer core is less than 0°C.

[0018] Despite the state of the art, it would be desirable to provide an adhesive system that has both the characteristics of an instant adhesive, such as the fast fix time found with cyanoacrylates and the ability to bond a wide range of substrates, such as metals and plastics, along with the improved adhesive strength found with (meth)acrylate compositions, across a larger variety and / or substrate selection. Additionally, it would be desirable for the two-part reactive adhesive to be strengthened so that the reaction product can withstand exposure to a variety of extreme conditions without sacrificing useful bond strength. Summary of the Invention [Means for solving the problem]

[0019] In one aspect, (a) a first part including a cyanoacrylate component and a peroxide catalyst; and (b) providing a two-part cyanoacrylate / free radically curable composition comprising a free radically curable component and a second part comprising a transition metal;

[0020] When mixed together, the peroxide catalyst of the first part initiates the cure of the free radically curable component of the second part, and the transition metal of the second part initiates the cure of the cyanoacrylate of the first part.

[0021] Importantly, there is further provided a core-shell impact modifier comprising, in at least one of the first or second parts, a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layer, and at least one polymer layer comprises a polymer that is a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer. There is further provided a composition in which, when mixed together, the peroxide catalyst initiates the cure of the free radically curable components and the transition metal initiates the cure of the cyanoacrylate, the (meth)acrylate-functionalized urethane resin having a polyurethane backbone that includes urethane linkages, at least a portion of which are formed from isophorane diisocyanate.

[0022] Because the first and second parts do not interact prior to use when mixed, the room temperature curable compositions provide good performance across substrates constructed from a wide variety of materials, superior durability performance over traditional two-part cyanoacrylate / free radical curable compositions with core-shell rubbers, improved fix time, and improved impact toughness performance over traditional free radical curable compositions. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 shows a bar graph of various adhesive systems used to bond metal (i.e., grit blasted mild steel and aluminum) substrates, shown on the X-axis, and impact toughness performance in Joules measured at 0 gap and 1 mm gap, shown on the Y-axis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] <Detailed Description> <Part A> The cyanoacrylate component includes H2C=C(CN)-COOR, where R is C 1~15 Alkyl, C 2~15 Alkoxyalkyl, C 3~15 Cycloalkyl, C 2~15 Alkenyl, C 7~15 Aralkyl, C 6~15 Aryl, C 3~15 Allyl and C 1~15 haloalkyl groups). Desirably, the cyanoacrylate monomer is selected from methyl cyanoacrylate, ethyl-2-cyanoacrylate ("ECA"), propyl cyanoacrylate, butyl cyanoacrylate (such as n-butyl-2-cyanoacrylate), octyl cyanoacrylate, allyl cyanoacrylate, β-methoxyethyl cyanoacrylate, and combinations thereof. Particularly desirable is ethyl-2-cyanoacrylate.

[0025] The cyanoacrylate component should be included in the Part A composition in an amount ranging from about 50% to about 99.98% by weight, with from about 90% to about 99% by weight of the Part A composition being preferred, and from about 92% to about 97% by weight being particularly preferred.

[0026] The peroxide catalyst in the Part A composition of the two-part adhesive system requires the use of a perbenzoate, such as t-butyl perbenzoate.

[0027] Typically, the amount of peroxide catalyst should range from about 0.001 weight percent to about 10.00 weight percent of the composition, desirably from about 0.01 weight percent to about 5.00 weight percent of the composition, such as from about 0.50 to 2.50 weight percent of the composition.

[0028] Additives may be included in the Part A composition of the adhesive system to impart physical properties such as improved fixation speed, improved shelf life stability, flexibility, thixotropy, increased viscosity, color, toughness, etc. Thus, such additives may be selected from accelerators, free radical stabilizers, anionic stabilizers, gelling agents, thickeners (such as PMMA), thixotropic agents (such as fumed silica), dyes, toughening agents, plasticizers, and combinations thereof.

[0029] To accelerate the cure of the cyanoacrylate component, one or more accelerators may also be used in the adhesive system, particularly in the Part A composition. Such accelerators may be selected from calixarenes and oxacalixarenes, silacrowns, crown ethers, cyclodextrins, poly(ethylene glycol) di(meth)acrylates, ethoxylated hydrated compounds, and combinations thereof.

[0030] Many calixarenes and oxacalixarenes are known and have been reported in the patent literature, for example, U.S. Patent Nos. 4,556,700, 4,622,414, 4,636,539, 4,695,615, 4,718,966, and 4,855,461, the disclosures of each of which are expressly incorporated herein by reference.

[0031] For example, with respect to calixarenes, those within the following structures are useful herein:

[0032] [ka] During the ceremony, R 1 is alkyl, alkoxy, substituted alkyl or substituted alkoxy; R 2 is H or alkyl; and n is 4, 6, or 8.

[0033] One particularly desirable calixarene is tetrabutyltetra[2-ethoxy-2-oxoethoxy]calix-4-arene.

[0034] Many crown ethers are known, including, for example, 15-crown-5, 18-crown-6, dibenzo-18-crown-6, benzo-15-crown-5-dibenzo-24-crown-8, dibenzo-30-crown-10, tribenzo-18-crown-6, asym-dibenzo-22-crown-6, dibenzo-14-crown-4, dicyclohexyl-18-crown-6, dicyclohexyl-24-crown-8, cyclohexyl-12-crown-4, 1,2-decaaryl-15-crown-5, 1,2-decaaryl-15-crown-6 ... ,2-naphtho-15-crown-5, 3,4,5-naphthyl-16-crown-5, 1,2-methyl-benzo-18-crown-6, 1,2-methylbenzo-5, 6-methylbenzo-18-crown-6, 1,2-t-butyl-18-crown-6, 1,2-vinylbenzo-15-crown-5, 1,2-vinylbenzo-18-crown-6, 1,2-t-butylcyclohexyl-18-crown-6, asym-dibenzo-22-crown-6 and 1,2-benzo-1,4-benzo-5-oxygen-20-crown-7. See U.S. Pat. No. 4,837,260 (Sato), the disclosure of which is hereby expressly incorporated herein by reference.

[0035] Of the silacrowns, again many are known and have been reported in the literature. For example, a typical silacrown can be represented in the structure:

[0036] [ka] During the ceremony, R 3 and R 4 is an organic group that does not itself cause polymerization of the cyanoacrylate monomer, and R 5is H or CH3, and n is an integer from 1 to 4. 3 and R 4 Examples of groups are R groups, alkoxy groups such as methoxy, and aryloxy groups such as phenoxy. 3 and R 4 The group may contain halogen or other substituents, an example of which is trifluoropropyl. However, R 4 and R 5 Groups that are not suitable as radicals are basic groups such as amino, substituted amino and alkylamino.

[0037] Specific examples of silacrown compounds useful in the compositions of the present invention include:

[0038] [ka] Dimethylsila-11-crown-4,

[0039] [ka] Dimethylsila-14-crown-5,

[0040] [ka] and dimethylsila-17-crown-6.

[0041] See, for example, US Pat. No. 4,906,317 (Liu), the disclosure of which is hereby expressly incorporated herein by reference.

[0042] Many cyclodextrins can be used in connection with the present invention. For example, the cyclodextrins described and claimed in U.S. Patent No. 5,312,864 (Wenz), the disclosure of which is hereby expressly incorporated herein by reference, as hydroxyl derivatives of α, β, or γ-cyclodextrin that are at least partially soluble in cyanoacrylates, are suitable choices as promoter components.

[0043] Additionally, poly(ethylene glycol) di(meth)acrylates suitable for use herein include those within the following structure:

[0044] [ka]

[0045] During the ceremony, n is greater than 3, for example, in the range of 3 to 12, and it is particularly preferred that n is 9. More specific examples include PEG 200 DMA (n is about 4), PEG 400 DMA (n is about 9), PEG 600 DMA (n is about 14), and PEG 800 DMA (n is about 19), where the number (e.g., 400) is the average molecular weight of the glycol portion of the molecule excluding the two methacrylate groups, expressed in grams / mole (i.e., 400 g / mol). A particularly preferred PEG DMA is PEG 400 DMA.

[0046] And of the ethoxylated hydric compounds (or ethoxylated fatty alcohols that may be used), suitable ones may be selected from those within the following structures:

[0047] [ka] In the formula, C mcan be a linear or branched alkyl or alkenyl chain, m is an integer from 1 to 30, e.g., 5 to 20, n is an integer from 2 to 30, e.g., 5 to 15, and R is H or an alkyl, e.g., C 1-6 It may be alkyl.

[0048] Additionally included are enhancers having the following structure: [ka] In the formula, R is hydrogen, C 1~6 Alkyl, C 1~6 Alkyloxy, alkylthioether, haloalkyl, carboxylic acids and their esters, sulfinic acids, sulfonic acids and sulfurous acids and esters, phosphinic acids, phosphonic acids and phosphorous acids and their esters, Z is a polyether bond, n is 1-12, p is 1-3 and is as defined above, R' is the same as R, and g is the same as n.

[0049] Particularly desirable chemicals within this class as accelerator components are the following: [ka] In the formula, the sum of n and m is 12 or more.

[0050] The accelerator should be included in the composition in an amount ranging from about 0.01% to about 10% by weight of the total composition, with a range of from about 0.1 to about 0.5% being preferred, and about 0.4% being particularly preferred.

[0051] Stabilizers useful for the Part A composition of the adhesive system include stabilizer packages that include free radical stabilizers, anionic stabilizers, and combinations thereof. The names and amounts of such stabilizers are well known to those skilled in the art. See U.S. Patent Nos. 5,530,037 and 6,607,632, the disclosures of each of which are incorporated herein by reference. Commonly used free radical stabilizers include hydroquinone, and commonly used anionic stabilizers include boron trifluoride, boron trifluoride-etherate, sulfur trioxide (and their hydrolysis products), and methanesulfonic acid.

[0052] <Part B> Free radically curable monomers for use in the Part B composition of the adhesive system include (meth)acrylate monomers, maleimide, itaconamide, or nadimide containing compounds, and combinations thereof.

[0053] (Meth)acrylate monomers for use in Part B of the adhesive system composition include many (meth)acrylate monomers, some of which are aromatic, others are aliphatic, and still others are cycloaliphatic. Examples of such (meth)acrylate monomers include polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and di(meth)acrylate, hydroxypropyl (meth)acrylate ("HPMA"), hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate ("TMPTMA"), diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TRIEGMA"), benzyl methacrylate, tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, di-(pentamethylene glycol) ... acrylate, tetraethylene diglycol diacrylate, diglycerol tetramethacrylate, tetramethylene dimethacrylate, ethylene dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, and bisphenol-A mono- and di(meth)acrylates, e.g., ethoxylated bisphenol-A (meth)acrylate ("EBIPMA"), bisphenol-F mono- and di(meth)acrylates, e.g., ethoxylated bisphenol-F (meth)acrylate, and di- or trifunctional (meth)acrylates, such as (meth)acrylate functional urethanes.

[0054] For example, examples of such (meth)acrylate-functionalized urethanes include tetramethylene glycol urethane acrylate oligomers and propylene glycol urethane acrylate oligomers.

[0055] Other (meth)acrylate-functionalized urethanes are urethane (meth)acrylate oligomers based on polyethers or polyesters reacted with aromatic, aliphatic, or cycloaliphatic diisocyanates and capped with hydroxyacrylates. Difunctional urethane acrylate oligomers are, for example, polyesters of hexanedioic acid and diethylene glycol terminated with isophorone diisocyanate and capped with 2-hydroxyethyl acrylate (CAS 72121-94-9), polypropylene glycol terminated with triene-2,6-diisocyanate and capped with 2-hydroxyethyl acrylate (CAS 37302-70-8), polyesters of hexanedioic acid and diethylene glycol terminated with 4,4'-methylenebis(cyclohexylisocyanate) and capped with 2-hydroxyethyl acrylate (CAS 69011-33-2), polyester of hexanedioic acid, 1,2-ethanediol, and 1,2 propanediol terminated with tolylene-2,4-diisocyanate and capped with 2-hydroxyethyl acrylate (CAS 69011-31-0), polyester of hexanedioic acid, 1,2-ethanediol, and 1,2 propanediol terminated with 4,4'-methylenebis(cyclohexylisocyanate) and capped with 2-hydroxyethyl acrylate (CAS 69011-32-1) and polytetramethylene glycol ether terminated with 4,4'-methylenebis(cyclohexylisocyanate) and capped with 2-hydroxyethyl acrylate.

[0056] Still other (meth)acrylate functionalized urethanes are monofunctional urethane acrylate oligomers such as polypropylene terminated with 4,4'-methylenebis(cyclohexylisocyanate) and capped with 2-hydroxyethyl acrylate and 1-dodecyl alcohol. They also include difunctional urethane methacrylate oligomers such as polytetramethylene glycol ether terminated with toluene-2,4-diisocyanate and capped with 2-hydroxyethyl methacrylate, polytetramethylene glycol ether terminated with isophorone diisocyanate and capped with 2-hydroxyethyl methacrylate, polytetramethylene glycol ether terminated with 4,4'-methylenebis(cyclohexylisocyanate) and capped with 2-hydroxyethyl methacrylate, polypropylene glycol terminated with tolylene-2,4-diisocyanate and capped with 2-hydroxyethyl methacrylate.

[0057] Maleimides, nadimides, and itaconimides include compounds having the following structures I, II, and III, respectively. [ka] In the formula, m is 1 to 15. P is 0 to 15; Each R 2 is independently selected from hydrogen or lower alkyl; J is a monovalent or polyvalent moiety containing organic or organosiloxane groups, and combinations of two or more thereof.

[0058] More specific representations of maleimides, itaconimides and nadimides include those corresponding to structures I, II or III, where m=1-6, p=0, R 2is independently selected from hydrogen or lower alkyl; J is a monovalent or polyvalent group selected from hydrocarbyl, substituted hydrocarbyl, heteroatom-containing hydrocarbyl, substituted heteroatom-containing hydrocarbyl, hydrocarbylene, substituted hydrocarbylene, heteroatom-containing hydrocarbylene-substituted heteroatom-containing hydrocarbylene, polysiloxane, polysiloxane-polyurethane block copolymer, and combinations of two or more thereof, and optionally is selected from a covalent bond, -O-, -S-, -NR-, -O ... C(O)-, -OC(O)-O-, -OC(O)-NR-, -NR-C(O)-, -NR-C(O)-O-, -NR-C(O)-NR-, -SC(O)-, -SC(O)-O-, -SC(O)-NR-, -S(O)-, -S(O)2-, -OS(O )2-, -OS(O)2-O-, -OS(O)2-NR-, -OS(O)-, -OS(O)-O-, -OS(O)-NR-, -O-NR-C(O)-, -O-NR-C(O)-O-, -O-NR-C(O)-NR-, -NR-OC(O)-, -NR- OC(O)-O-, -NR-OC(O)-NR-, -O-NR-C(S)-, -O-NR-C(S)-O-, -O-NR-C(S)-NR-, -NR-OC(S)-, -NR-OC(S)-O-, -NR-OC(S)-NR-, -OC(S)-, - OC(S)-O-, -OC(S)-NR-, -NR-C(S)-, -NR-C(S)-O-, -NR-C(S)-NR-, -SS(O)2-, -SS(O)2-O-, -SS(O)2-NR-, -NR-OS(O)-, -NR-OS(O)-O-, and one or more linkers selected from -NR-OS(O)-NR-, -NR-OS(O)2-, -NR-OS(O)2-O-, -NR-OS(O)2-NR-, -O-NR-S(O)-, -O-NR-S(O)-O-, -O-NR-S(O)-NR-, -O-NR-S(O)2-O-, -O-NR-S(O)2-NR-, -O-NR-S(O)2-, -OP(O)R2-, -SP(O)R2-, -NR-P(O)R2- (wherein each R is independently hydrogen, alkyl, or substituted alkyl).

[0059] When one or more of the above monovalent or polyvalent groups include one or more of the above linkers to form a "J" adduct of a maleimide, nadimide or itaconimide group, as will be readily recognized by one of skill in the art, e.g., oxyalkyl, thioalkyl, aminoalkyl, carboxylalkyl, oxyalkenyl, thioalkenyl, aminoalkenyl, carboxyalkenyl, oxyalkynyl, thioalkynyl, aminoalkynyl, carboxyalkynyl, oxycycloalkyl, thiocycloalkyl, aminocycloalkyl, carboxycycloalkyl, oxychloroalkenyl, thiocycloalkenyl, aminocycloalkenyl, carboxycycloalkenyl, heterocyclic, oxyheterocyclic, thioheterocyclic, aminoheterocyclic, carboxyheterocyclic, oxyaryl, thioaryl, aminoaryl, carboxyaryl, heteroaryl, oxyheteroaryl, thioheteroaryl, aminoheteroaryl, carboxyheteroaryl, oxyalkylaryl, thioalkylaryl, aminoalkylaryl, carboxyalkylaryl, oxyarylalkyl, thioarylalkyl, amino arylalkyl, carboxyarylalkyl, oxyarylalkenyl, thioarylalkenyl, aminoarylalkenyl, carboxyarylalkenyl, oxyalkenylaryl, thioalkenylaryl, aminoalkenylaryl, carboxyalkenylaryl, oxyarylalkynyl, thioarylalkynyl, aminoarylalkynyl, carboxyarylalkynyl, oxyalkynylaryl, thioalkynylaryl, aminoalkynylaryl or carboxyalkynylaryl, oxyalkylene, thioalkylene, aminoalkylene, carboxyalkylene, oxyalkenylene, thioalkenylene, aminoalkenylene, carboxyalkenylene, oxyalkynylene, thioalkynylene, aminoalkynylene, carboxyalkynylene, oxycycloalkylene, thiocycloalkylene, aminocycloalkylene, carboxycycloalkylene, oxycycloalkenylene, thiocycloalkenylaminoalkylarylene, carboxyalkylarylene, oxyarylalkylene, thioarylalkylene, aminoarylalkylene,A variety of linkers can be made, such as carboxyarylalkylenes, oxyarylalkenylenes, thioarylalkenylenes, aminoarylalkenylenes, carboxyarylalkenylenes, oxyalkenylarylenes, thioalkenylarylenes, aminoalkenylarylenes, carboxyalkenylarylenes, oxyarylalkynylenes, thioarylalkynylenes, aminoarylalkynylenes, carboxyarylakynylenes, oxyalkynylarylenes, thioalkynylarylenes, aminoalkynylarylenes, carboxyalkynylarylenes, heteroarylenes, oxyheteroarylenes, thioheteroarylenes, aminoheteroarylenes, carboxyheteroarylenes, heteroatom-containing divalent or polyvalent cyclic moieties, oxyheteroatom-containing divalent or polyvalent cyclic moieties, thioheteroatom-containing divalent or polyvalent cyclic moieties, aminoheteroatom-containing divalent or polyvalent cyclic moieties, carboxyheteroatom-containing divalent or polyvalent cyclic moieties, disulfides, sulfonamides, etc.

[0060] In another embodiment, the maleimides, nadimides, and itaconimides contemplated for use in the practice of the present invention have structures I, II, and III, where m=1-6, p=0-6, and J is Saturated straight or branched chain alkyls having an optional substituted aryl moiety as a substituent on the alkyl chain or as part of the backbone of the alkyl chain, the alkyl chain having up to about 20 carbon atoms:

[0061] Structure - (C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4 )2-(C(R 3 )2) e -, -(C(R 3 )2) d -C(R 3 )-C(O)O-(C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4 )2-(C(R3 )2) e -O(O)C-(C(R 3 )2) e -or-(C(R 3 )2) d -C(R 3 )-O(O)C-(C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4 )2-(C(R 3 )2) e -C(O)O-(C(R 3 )2) e -(In the formula, each R 3 are independently hydrogen, alkyl, or substituted alkyl; Each R 4 are independently hydrogen, lower alkyl or aryl; d=1-10, e=1-10, and f=1-50:

[0062] Structure [(CR2) r -O-] f -(CR2) s -(In the formula, each R is independently hydrogen, alkyl, or substituted alkyl; r=1-10, s=1-10, and and f is as defined above.

[0063] structure [ka] (In the formula, each Ar is a mono-, di- or tri-substituted aromatic or heteroaromatic ring having in the range of 3 to 10 carbon atoms; Z is a saturated straight chain or branched chain alkylene, optionally containing a saturated cyclic moiety as a substituent on the alkylene chain or as part of the backbone of the alkylene chain;

[0064] Structure-[(CR2) r -O-] q -(CR2) s - (In the formula, each R is independently hydrogen, alkyl, or substituted alkyl, and r and s are each defined above; and q is in the range of 1 to 50.

[0065] structure [ka] (In the formula, each R is independently hydrogen, alkyl, or substituted alkyl; t is in the range of 2 to 10, u is in the range of 2 to 10, Ar is as defined above. A di- or tri-substituted aromatic moiety having:

[0066] structure [ka]

[0067] During the ceremony, each R is independently hydrogen, alkyl, or substituted alkyl; t=2-10, k=1, 2 or 3, g=1~about 50, Each Ar is as defined above, E is -O- or -NR 5 - and R 5 is hydrogen or lower alkyl, W is a linear or branched alkyl, alkylene, oxyalkylene, alkenyl, alkenylene, oxyalkenylene, ester, or polyester, -(C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4)2-(C(R 3 )2) e -, -(C(R 3 )2) d -C(R 3 )-C(O)O-(C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4 )2-(C(R 3 )2) e -O(O)C-(C(R 3 )2) e -or-(C(R 3 )2) d -C(R 3 )-O(O)C-(C(R 3 )2) d -[Si(R 4 )2-O] f -Si(R 4 )2-(C(R 3 )2) e -C(O)O-(C(R 3 )2) e -(In the formula, each R 3 are independently hydrogen, alkyl, or substituted alkyl; Each R 4 are independently hydrogen, lower alkyl or aryl; d=1-10, e=1-10, and f=1-50) is a siloxane structure having an aromatic group:

[0068] Structure-[(CR2) r -O-] f -(CR2) s - (In the formula, each R is independently hydrogen, alkyl, or substituted alkyl; r=1-10, s=1-10, and f is as defined above, optionally containing substituents selected from hydroxy, alkoxy, carboxy, nitrile, cycloalkyl or cycloalkenyl.

[0069] Structure R 7 -UC(O)-NR 6 -R 8 -NR 6 -C(O)-(OR 8 -OC(O)-NR 6 -R 8 -NR 6 -C(O) v -UR 8 - (In the formula, Each R 6 are independently hydrogen or lower alkyl; Each R 7 are independently an alkyl, aryl, or arylalkyl group having 1 to 18 carbon atoms; Each R 8 is an alkyl or alkyloxy chain having up to about 100 atoms in the chain, optionally substituted with Ar; U is -O-, -S-, -N(R)- or -P(L) 1,2 - and wherein R is defined above, and each L is independently =O, =S, -OR, or -R; v=0-50.) having a urethane group:

[0070] polycyclic alkenyl; or a mixture of any two or more thereof.

[0071] In more specific descriptions of such maleimide-, nadimide-, and itaconimide-containing compounds of structures I, II, and III, respectively, each R is independently hydrogen or lower alkyl (C 1~4 etc.), where -J- comprises a branched chain alkyl, alkylene, alkylene oxide, alkylene carboxyl or alkylene amide species having sufficient length and branching to render the maleimide, nadimide and / or itaconimide compound liquid, and m is 1, 2 or 3.

[0072] Particularly desirable maleimide-containing compounds include those having two maleimide groups with an aromatic group between them, such as a phenyl, biphenyl, bisphenyl or naphthyl linkage.

[0073] In addition to the free radical curable component, Part B also includes a transition metal compound. A non-exhaustive list of representative examples of transition metal compounds are copper, vanadium, cobalt, and iron compounds. For example, with respect to copper compounds, copper compounds in which copper is in a 1+ or 2+ valence state are preferred. A non-exhaustive list of examples of such copper(I) and (II) compounds includes copper(II) 3,5-diisopropylsalicylate hydrate, copper bis(2,2,6,6-tetramethyl-3,5-heptanedionate), copper(II) phosphate hydroxide, copper(II) chloride, copper(II) acetate monohydrate, tetrakis(acetonitrile)copper(I) hexafluorophosphate, copper(II) formate hydrate, tetrakisacetonitrile copper(I) triflate, copper(II) tetrafluoroborate, copper(II) perchlorate, tetrakis(acetonitrile)copper(I) tetrafluoroborate, copper(II) hydroxide, copper(II) hexafluoroacetylacetonate hydrate, and copper(II) carbonate. These copper (I) and (II) compounds, when dissolved or suspended in a carrier medium such as a (meth)acrylate, are present in the solution or suspension at a concentration of about 100 ppm to about 5,000 ppm, for example about 500 ppm to about 2,500 ppm, for example about 1,000 ppm.

[0074] As for vanadium compounds, vanadium compounds in which vanadium is in the valence states of 2+ and 3+ are preferred. Examples of such vanadium(III) compounds include vanadyl naphthanate and vanadyl acetylacetonate. These vanadium(III) compounds should be used in an amount of 50 ppm to about 5,000 ppm, for example about 500 ppm to about 2,500 ppm, for example about 1,000 ppm.

[0075] As for the cobalt compound, it is preferable that the cobalt compound has a valence state of 2+. Examples of such cobalt (II) compounds include cobalt naphthenate, cobalt tetrafluoroborate, and cobalt acetylacetonate. These cobalt (II) compounds should be used in an amount of about 100 ppm to about 1000 ppm.

[0076] As for the iron compound, an iron compound in which iron is in a valence state of 3+ is preferred. Examples of such iron(III) compounds include iron acetate, iron acetylacetonate, iron tetrafluoroborate, iron perchlorate, iron chloride, etc. These iron compounds should be used in an amount of about 100 ppm to about 1000 ppm.

[0077] At least one of the first or second parts of the two-part composition of the present invention includes a polymer that itself includes a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer being a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged along the copolymer from primarily monomer (A) to primarily monomer (B), and when mixed together, the peroxide catalyst initiates the cure of the free radically curable component and the transition metal initiates the cure of the cyanoacrylate component. A core-shell impact modifier is included that includes a core-shell impact modifier ...

[0078] The core-shell impact modifier should comprise particles having a particle size between 170-350 nm and a pH between 6-7.5, comprising one polymeric rubber core comprising at least partially crosslinked isoprene or butadiene and optionally styrene, and at least two polymeric layers, at least one of which is an outermost thermoplastic shell layer having a Tg greater than 25°C, each layer having a different polymer composition. The core-shell impact modifier should include a polymeric rubber core, surrounded by a polymeric layer, the polymeric core layer having a glass transition temperature below 0° C. and a different polymer composition than the polymeric rubber core, said polymeric core layer being a gradient zone.

[0079] The core-shell impact modifier should include at least one polymeric core layer and at least two polymeric shell layers, where the polymeric core layer has a different composition than the polymeric shell layers, each shell layer having a different polymer composition than the other shell layers, and at least one polymeric shell layer is a gradient zone.

[0080] The core-shell impact modifier should comprise a polymeric rubber core having a glass transition temperature below 0°C, e.g., below about -10°C, desirably below about -20°C, advantageously below about -25°C, and most advantageously below about -40°C, such as between about -80°C and about -40°C.

[0081] The core-shell impact modifier should include a polymeric rubber core composed of one or more of isoprene or butadiene homopolymers, isoprene-butadiene copolymers, copolymers of isoprene with up to 98 weight percent of a vinyl monomer, and copolymers of butadiene with up to 98 weight percent of a vinyl monomer. The vinyl monomers can be styrene, alkylstyrene, acrylonitrile, alkyl (meth)acrylates, or butadiene or isoprene. Desirably, the core should be composed of one of polybutadiene, copolymers of butadiene and styrene, or terpolymers of methyl methacrylate, butadiene and styrene.

[0082] In some embodiments, the core may also be covered by a core layer, which means that the polymer composition of the core layer has a glass transition temperature (Tg) below 0° C., for example, below about −10° C., desirably below about −20° C., and advantageously below about −25° C. Desirably, the core layer is a gradient polymer.

[0083] The core-shell impact modifier should have multiple shells, preferably two shells, with at least the outer shell in contact with the thermoplastic matrix having a Tg greater than about 25°C, such as greater than about 50°C.

[0084] The shell of the core-shell impact modifier may be composed of one or more of styrene homopolymer, alkylstyrene homopolymer or methyl methacrylate homopolymer or copolymers containing at least 70% by weight of the above monomers and at least one comonomer selected from other of the above monomers, another alkyl (meth)acrylate, vinyl acetate and acrylonitrile. The shell may be functionalized, for example, with anhydrides of unsaturated carboxylic acids, unsaturated carboxylic acids and unsaturated epoxides, such as maleic anhydride, (meth)acrylic acid glycidyl methacrylate, hydroxyethyl methacrylate and alkyl (meth)acrylamides.

[0085] A gradient copolymer is created by occupying a position between two layers, creating a gradient zone that is enriched on one side with the monomer / polymer from the adjacent layer and on the other side with the different monomer / polymer that will form the next layer. A gradient zone between the core and shell, or between two polymer shells, can be produced, for example, by monomers with different copolymerization parameters, or by running the reaction in semi-continuous mode under starved feed conditions, where the rate of monomer addition is slower than the reaction rate. However, a gradient polymer cannot be the outermost layer of a core-shell particle.

[0086] The monomers used to form the gradient polymer are selected from the monomers cited for the core and each shell based on the functionality of the adjacent layers.

[0087] The Young's modulus of the polymer rubber core is always less than that of the other polymeric layers. The Young's modulus of the layer containing the gradient polymer is always less than that of the outermost layer.

[0088] The core-shell impact modifier must be in the form of microparticles having a rubber core and at least one thermoplastic shell, the particle size being generally less than 1 μm, advantageously between 50 nm and 500 nm, preferably between 100 nm and 400 nm, most preferably between 150 nm and 350 nm, advantageously between 170 nm and 350 nm.

[0089] Core-shell impact modifiers can be prepared by emulsion polymerization. For example, a suitable method is a two-stage polymerization technique in which the core and shell are produced in two successive emulsion polymerization stages. If there are more shells, another emulsion polymerization stage follows. The graft copolymer is obtained by graft polymerizing a monomer or mixture of monomers containing at least an aromatic vinyl, an alkyl methacrylate or an alkyl acrylate in the presence of a latex containing a butadiene-based rubber polymer. For details regarding the preparation of such core-shell impact modifiers, see the '036 and '314 patents. Commercially available examples of such core-shell impact modifiers are available under the trade name CLEARSTRENGTH from Arkema Inc., Cary, NC. Arkema describes CLEARSTRENGTH XT100, for example, as a methyl methacrylate-butadiene-styrene core-shell toughening agent that is compatible with a wide variety of monomers, easily dispersible in most liquid resin systems, and provides a toughening effect over a wide range of use temperatures while limiting the impact on viscosity.

[0090] The core-shell impact modifier may be present in either or both of Part A or Part B. The core-shell impact modifier should be present in either or both of Part A or Part B in an amount of from about 2 weight percent to about 20 weight percent.

[0091] As mentioned above, additives can be included in either or both of the Part A or Part B compositions to affect various performance characteristics.

[0092] Fillers that may be contemplated for use include, for example, aluminum nitride, boron nitride, silicon carbide, diamond, graphite, beryllium oxide, magnesia, silica such as fumed or fused silica, alumina, perfluorinated hydrocarbon polymers (i.e., TEFLON®), thermoplastic polymers, thermoplastic elastomers, mica, glass powders, etc. Preferably, the particle size of these fillers will be about 20 microns or less.

[0093] With respect to silica, the silica may have an average particle size in the nanoparticle size range, i.e., 10 -9 They have an average particle size of the order of meters. Silica nanoparticles can be pre-dispersed in epoxy resins and selected from those available under the trade name NANOPOCRYL from Nanoresins, Germany. NANOCRYL is the trade name for a family of silica nanoparticle reinforced (meth)acrylate products. The silica phase consists of surface-modified synthetic SiO2 nanospheres with diameters below 50 nm and a very narrow particle size distribution. The SiO2 nanospheres are agglomerate-free dispersions in the (meth)acrylate matrix, resulting in low viscosities for resins containing up to 50 wt.% silica.

[0094] The silica component should be present in an amount ranging from about 1 to about 60 weight percent, for example, from about 3 to about 30 weight percent, and desirably from about 5 to about 20 weight percent, based on the total weight of the composition.

[0095] Thickeners are also useful.

[0096] Stabilizers and inhibitors may also be used to control premature decomposition of the peroxide and prevent polymerization. Inhibitors may be selected from hydroquinone, benzoquinone, naphthoquinone, phenanthroquinone, anthraquinone, and substituted compounds thereof. Various phenols, such as 2,6-di-t-butyl-4-methylphenol, may also be used as inhibitors. Inhibitors may be used in amounts of about 0.1 weight percent to about 1.0 weight percent of the total composition without adversely affecting the cure rate of the polymerizable adhesive composition.

[0097] In practice, each of the compositions of Part A and Part B is contained in a separate containment container within the device prior to use, and upon use, the two parts emerge from the container, are mixed and applied to a substrate surface. The container may be a chamber of a dual-chamber cartridge, in which the separate parts are advanced through a chamber with a plunger, through an orifice (which may be common or adjacent), and then through a mixing dispense nozzle. Alternatively, the container may be a coaxial or side-by-side pouch, which may be cut or torn and its contents mixed and applied to a substrate surface.

[0098] The compositions of the present invention, when placed between two substrates spaced about 1 mm apart and cured into a reaction product, exhibit a drop impact strength of greater than about 40 Joules.

[0099] The compositions of the present invention, when cured into a reaction product, exhibit greater drop impact strength on substrates bonded together in 1 mm spacing than on substrates bonded together in 0 mm spacing.

[0100] The invention will be more readily understood by consideration of the following examples. EXAMPLES

[0101] References to ECA mean ethyl-2-cyanoacrylate.

[0102] For control purposes, adhesive systems were prepared with reference to Table 1. Part A contained ECA mixed with a combination of LEVAPREN900, t-BPB and boron trifluoride / methanesulfonic acid, and Part B contained a combination of acrylated urethane ester, HPMA, and CN2003EU as the (meth)acrylate component, to which was added the previously described hydrated copper chloride and filler package.

[0103] [Table 1]

[0104] [Table 2]

[0105] The lA-lB system was mixed and dispensed in a 0 mm gap configuration and a 1 mm gap configuration onto grit blasted mild steel lap shears having the substrates described joined in an overlapped offset fashion with the adhesive system placed between the substrates in the overlapped offset portion. The substrates were 0.120±0.005 inches thick.

[0106] As described above, 1A-2B, 1A-3B, 1A-4B, and 1A-5B systems were mixed and dispensed in 0 mm and 1 mm gap configurations onto grit blasted mild steel lap shears having the above substrates bonded in an overlapping offset manner using adhesive systems placed between the substrates at the overlapping offset portions. The substrate thickness was 0.120±0.005 inches.

[0107] Table 2 below records the drop impact strength performance of these systems. [Table 3]

[0108] The 1A-1B system demonstrated drop impact toughness performance of 14.1 Joules at 0 mm gap and 44.6 Joules at 1 mm gap, based on an average of 5 repetitions, as recorded in Table 2. This observation correlates with a greater than 3-fold increase in strength when a 1 mm gap was introduced between the bonded substrates. The remaining systems showed perfectly moderate performance, with only one other showing improvement in the spaced configuration. (See Figure 1)

Claims

1. (a) a first part comprising a cyanoacrylate component and a peroxide catalyst; and (b) a two-part curable composition comprising a free radically curable component and a second part comprising a transition metal, at least one of the first part or the second part further comprising a core-shell impact modifier comprising 2 weight percent to 20 weight percent in the part of a polymer core and at least two polymer layers surrounding the core; The core-shell impact modifier comprises a polymeric rubber core comprising at least partially crosslinked isoprene or butadiene and optionally styrene, and at least two polymeric layers, at least one of which is an outermost thermoplastic shell layer having a Tg greater than 25° C., each layer having a different polymeric composition, the particles having a particle size between 170-350 nm and a pH between 6-7.5; at least one polymer layer comprises a polymer that is a gradient polymer, a gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer; A composition in which, when mixed together, the peroxide catalyst initiates the cure of the free radically curable component and the transition metal initiates the cure of the cyanoacrylate.

2. The cyanoacrylate component is H 2 2. The composition of claim 1 comprising a C=C(CN)-COOR group, where R is selected from alkyl, alkoxyalkyl, cycloalkyl, alkenyl, aralkyl, aryl, allyl, and haloalkyl groups.

3. The composition of claim 1 , wherein the peroxide catalyst comprises a perbenzoate.

4. The composition of claim 1, wherein the peroxide catalyst is t-butyl perbenzoate.

5. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core surrounded by a polymeric layer, the polymeric core layer having a glass transition temperature below 0°C and a different polymer composition than the polymeric rubber core, the polymeric core layer being a gradient zone.

6. 10. The composition of claim 1, wherein the core-shell impact modifier comprises at least one polymeric core layer and at least two polymeric shell layers, the polymeric core layer having a different composition than the polymeric core and shell layers, each shell layer having a different polymer composition than the other shell layers, and at least one polymeric shell layer is a gradient zone.

7. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core having a glass transition temperature of less than -40.degree.

8. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core having a glass transition temperature of from -80°C to -40°C.

9. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core comprised of polybutadiene.

10. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core composed of butadiene and styrene.

11. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core composed of methyl methacrylate, butadiene and styrene.

12. 10. The composition of claim 1, wherein the core-shell impact modifier is present in the first part.

13. 10. The composition of claim 1, wherein the core-shell impact modifier is present in the second part.

14. The composition of claim 1, wherein the peroxide catalyst is present in an amount from 0.01 weight percent to 10 weight percent based on the cyanoacrylate component.

15. 2. The composition of claim 1, wherein the free radical curable component is a (meth)acrylate component selected from the group consisting of polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and di(meth)acrylate, hydroxypropyl (meth)acrylate, hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, benzyl methacrylate, tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, di-(pentamethylene glycol) dimethacrylate, tetraethylene diglycol diacrylate, diglycerol tetramethacrylate, tetramethylene dimethacrylate, ethylene dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, ethoxylated bisphenol-A (meth)acrylate, ethoxylated bisphenol-F (meth)acrylate, and methacrylate-functional urethanes.

16. 2. The composition of claim 1, wherein the transition metal comprises a member selected from the group consisting of copper, vanadium, cobalt and iron.

17. 2. The composition of claim 1, wherein the first part is contained in a first chamber of a dual chamber syringe and the second part is contained in a second chamber of the dual chamber syringe.

18. The composition of claim 1 , wherein the second part further comprises at least one of a plasticizer and a filler.

Citation Information

Patent Citations

  • New core shell particle multistage polymer powder, method for production thereof, and composition comprising the same

    JP2012126901A

  • Two-component cyanoacrylate / free radical curing adhesive system

    JP2015509126A